Pengembangan UMKM Desa Lopo Kecamatan Batudaa Pantai Kabupaten Gorontalo sebagai Kawasan Ekonomi Khusus (KEK) Teluk Tomini - Abdul, Nurnaningsih Nico; Mutmainnah, Nur; Saputra, Wahyu (Universitas Negeri Gorontalo, 2024)
The UNG Architectural Engineering Department supports UNG's big program which is committed to realizing the development of Kawasan Ekonomi Khusus (KEK) in the coastal area of Tomini Bay through the Merdeka Belajar Kampus Merdeka (MBKM) activity program integrated with KKN through one of its programs increasing economic independence through the development of UMKM. The implementation method is done by collecting data, analysis, and realization. UMKM in desa Lopo did not develop well due to capital and marketing problems which were classified into three types of UMKM products: Kue Bilibidu, Kue Dumalo, dan Abon Ikan. To maximize its development with promotion and marketing; make an attractive product packaging logo, make a video, then promote it to the product on social media and spread marketing to several places outside desa Lopo. It is hoped that the public can give birth to further innovations and get brand protection by registering Hak Kekayaan Intelektual (HKI).